Poverty in rural India: Issues and perspectives - Sharma, Subhash; Mishra, Devendra (2010)
Nearly three fourth of India's 300 million poor live in rural areas, most of them are daily wagers, landless labourers and self-employed householders. A large number of these people live in the country's semi-arid tropical region. A major cause of poverty among India's rural people, both individuals and communities, is lack of access to productive assets and financial resources. High levels of illiteracy, inadequate health care and extremely limited access to social services are common among poor rural people. Micro-enterprise development, which could generate income and enable poor people to improve their living conditions, has only recently become a focus of the government. It is suggested here that a proactive facilitator state and a regulated market should mutually work in a complementary and interdependent way to provide maximum opportunities to the rural poor in India. Poverty is not a technical problem, rather a socio-economic, spatial and political problem; hence it urgently requires a radical socio-economic, spatial and political solution. - Reproduced.
Keywords: Poverty - India; Poverty